Elemental geochemistry and organic facies of selected cretaceous coals from the Benue Trough basin in Nigeria: Implication for paleodepositional environments. (March 2022) - Akinyemi, Segun A.; Adebayo, Olajide F.; Madukwe, Henry Y.; Kayode, Ayobami T.; Aturamu, Adeyinka O.; OlaOlorun, Olusola A.; Nyakuma, Bemgba B.; Jauro, Aliyu; Gitari, Wilson M.; Mudzielwana, Rabelani; Hower, James C.
Abstract: Benue Trough basin is geologically subdivided into three segments. It consists of marine and continental sediments that are affected by folding movements. In the upper section, the continental coal-bearing Campano-Maastrichtian-age is found within Gombe Sandstone and the Cenozoic Kerri-Kerri Formation of the Tertiary. In the middle segment, the late Turonian/early Santonian coal-bearing Awgu Formation lies conformably on the Ezeaku Formation. In the lower part, shales at Nkporo mark marine incursion and deposition of the Maastrichtian Mamu Formation coal measures. Cretaceous coal samples taken from the three segments of Benue Trough basin were examined using ultimate and proximate, organic petrographic, x-ray fluorescence (XRF) and laser ablation-induced coupled plasma spectroscopy (LA-ICPMS) analytical techniques. Results of trace element ratios, Ce/Ce* values ("where Ce* is the theoretical Ce value derived from a chondrite-normalized rare earth element (REE) pattern"), authigenic uranium values, and low hydrogen content indicate deposition under oxic to suboxic conditions. However, the V/Ni and V/Sc ratios indicate under oxic, suboxic to reducing conditions. The Y/Ho values for selected coals are lower than the range for seawater, indicating terrigenous influence. The Sr/Ba values indicate low influence of saline water during deposition and a strong continental rather than marine influence. High value of vitrinite and low proportion of liptinite/intertinite suggest that peat in the study areas were situated on the irregular basin floor where sediment thicknesses vary from place to place thus the depositional environments shifted causing mineral matter filling in coal. Based on the tissue preservation index (TPI) and gelification index (GI), LFB, CHK, OKB, LMZ, IMG; and ENG (high GI and high TPI) were deposited in telmatic facies; wet-forest swamps with rapid organic matter accumulation. This trend indicates mild humification and strong gelification of plant tissues which ascribed to high rate of subsidence with wood- and bark-derived telovitrinite. The MGA peats were deposited in terrestrial facies in a dry-forest swamp with wood-derived telo-inertinite. The coal samples code-named IMG and ENG were deposited in planar margin mires. However, coal samples code-named LFB, CHK and LMZ were deposited in planar central mires. Lastly, OKB and MGA were deposited in transitional-wet and transitional-dry mire. The low V and Ni concentrations, low H/C, high O/C, high C/N, and very low N/C ratios <0.05 implies Type III land-plant organic matter that is not oil-prone. The depositional environments interpretations of investigated coal seams indicate that the coals were deposited within a telmatic, limnic, limno-telmatic and open march zone. Generally, a combination of results from inorganic geochemistry and organic petrology is required for precise and all-inclusive determination of coal depositional environments. Graphical abstract: Image 1 Highlights: Paleoredox parameters, Ce/Ce* values, authigenic U values, and low H2 content suggest oxic to suboxic depositional conditions. Sr/Ba values indicate low influence of saline water during deposition and a strong continental rather than marine influence. The Y/Ho values for selected coals are lower than the range for seawater, indicating terrigenous influence. The studied coals contain Type III land-plant organic matter that is not oil-prone.